Modern weapons and military equipment for issue 3/2013 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Swallow flies again; Published new tactical and technical data for the MiG-29M / M2; Saab develops deck Sea Gripen and optionally unmanned Gripen OP; Chengdu presented the model two-seater version of the aircraft FC-1; Viewed transport plane C296W; The US Army chose Bell V-280 Valor for your JMR-TD program.